2010
DOI: 10.1073/pnas.0908869107
|View full text |Cite
|
Sign up to set email alerts
|

MLCK-dependent exchange and actin binding region-dependent anchoring of ZO-1 regulate tight junction barrier function

Abstract: The perijunctional actomyosin ring contributes to myosin light chain kinase (MLCK)-dependent tight junction regulation. However, the specific protein interactions involved in this process are unknown. To test the hypothesis that molecular remodeling contributes to barrier regulation, tight junction protein dynamic behavior was assessed by fluorescence recovery after photobleaching (FRAP). MLCK inhibition increased barrier function and stabilized ZO-1 at the tight junction but did not affect claudin-1, occludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
221
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(240 citation statements)
references
References 28 publications
17
221
0
1
Order By: Relevance
“…Expression of either full-length EGFP-ZO-1 or EGFP-ZO-1 ΔABR increased the peak TER, although this was 20%±1.0% greater in monolayers that expressed full-length EGFP-ZO-1 relative to those expressing EGFP-ZO-1 ΔABR . This suggests that ABR-mediated interactions play a role in initial barrier formation, consistent with their established role in barrier regulation (Yu et al, 2010). In contrast, induction of EGFP-ZO-1 ΔU5-GuK expression reduced the TER relative to that in uninduced controls (Fig.…”
Section: Zo-1 U5-guk-domain-mediated Interactions Are Necessary For Esupporting
confidence: 67%
See 2 more Smart Citations
“…Expression of either full-length EGFP-ZO-1 or EGFP-ZO-1 ΔABR increased the peak TER, although this was 20%±1.0% greater in monolayers that expressed full-length EGFP-ZO-1 relative to those expressing EGFP-ZO-1 ΔABR . This suggests that ABR-mediated interactions play a role in initial barrier formation, consistent with their established role in barrier regulation (Yu et al, 2010). In contrast, induction of EGFP-ZO-1 ΔU5-GuK expression reduced the TER relative to that in uninduced controls (Fig.…”
Section: Zo-1 U5-guk-domain-mediated Interactions Are Necessary For Esupporting
confidence: 67%
“…On the contrary, other studies have demonstrated a regulatory function whereby the ABR stabilizes ZO-1 at the tight junction and is necessary for myosin light chain kinase (MLCK)-dependent ZO-1 trafficking and barrier regulation (Yu et al, 2010). The data here further support a model in which, without the ABR, ZO-1 scaffolding functions are diminished and ZO-1 is unable to effectively facilitate complex interactions (Shen et al, 2008;Yu et al, 2010). Nevertheless, our results indicate that a direct link with F-actin through the ABR is required for ZO-1 to regulate epithelial morphogenesis in some environments.…”
Section: δU5-gukmentioning
confidence: 97%
See 1 more Smart Citation
“…cZNA localization does not exactly mimic full length ZO-1 expression, nor does it restore the phenotypic, wavy junctions of wild type MDCK cells or dKD cells expressing full length ZO-1 (Fig. 1C) (Fanning et al, 2012), therein confirming that the C-terminal region (aa 888-1746) has a role in the orchestrating the typical architecture of the AJC in these cells (Yu et al, 2010). However, we did not investigate these differences further because they did not correlate with changes in the permeability of MDCK cells (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…IEL migration assays into Caco-2 BBe monolayers (24,26) were performed placing flow cytometry-sorted IELs in the upper chamber of the Transwell and fixing the filters at various time points. Stable cell lines expressing pSUPER vectors containing occludin (36) or ZO-1 (26) targeting sequence resulted in the suppression of 90% of target protein expression in Caco-2 BBe cells (46).…”
Section: Methodsmentioning
confidence: 99%